The Qingdao Preschooler Facial Expression Set: Acquisition and Validation of Chinese Children’s Facial Emotion Stimuli - Chen, Jie; Zhang, Yulin; Zhao, Guozhen (Frontiers in Psychology, 2021)
Traditional research on emotion-face processing has primarily focused on the expression of basic emotions using adult emotional face stimuli. Stimulus sets featuring child faces or emotions other than basic emotions are rare. The current study describes the acquisition and evaluation of the Qingdao Preschooler Facial Expression (QPFE) set, a facial stimulus set with images featuring 54 Chinese preschoolers’ emotion expressions. The set includes 712 standardized color photographs of six basic emotions (joy, fear, anger, sadness, surprise, and disgust), five discrete positive emotions (interest, contentment, relief, pride and amusement), and a neutral expression. The validity of the pictures was examined based on 43 adult raters’ online evaluation, including agreement between designated emotions and raters’ labels as well as intensity and representativeness scores. Overall, these data should contribute to the developmental and cross-cultural research on children’s emotion expressions and provide insights for future research on positive emotions.